KAJIAN EKOKRITIK TERHADAP EKSPLOITASI ALAM DALAM NOVEL KAOK BURUNG GAGAK DI KAHAYAN KARYA HAN GAGAS - Ayu, Novi Zurianti; Wahyusari, Ahada; Mustado, Maulida; Malik, Abdul; Irawan, Dody; Leoni, Tessa Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and describe various forms of environmental damage caused by the exploitation of natural resources as depicted in the novel Kaok Burung Gagak di Kahayan by Han Gagas. The research uses an ecocritical approach with a qualitative type of research using a descriptive method. The main instrument in this study is the researcher themself, supported by data analysis guidelines in the form of tables. Data collection was done through an in-depth reading of the novel Kaok Burung Gagak di Kahayan as the research object, then continued with recording, grouping, and determining data relevant to the research focus. After that, the data were analyzed using content analysis techniques, which included data reduction, data presentation, and drawing conclusions. The research results show that Han Gagas's novel Kaok Burung Gagak in Kahayan represents various forms of environmental damage that occur as a result of natural resource exploitation activities.